Do Online Homework Tools Improve Student Results in Principles of Microeconomics Courses? - Lee, William; Courtney, Richard H; Balassi, Steven J (American Economic Review, 2010)
Do Online Homework Tools Improve Student Results in Principles of Microeconomics Courses? by William Lee, Richard H. Courtney and Steven J. Balassi. Published in volume 100, issue 2, pages 283-86 of American Economic Review, May 2010